(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
This article examines the proposal of the Ministry of Defense of the Republic of Uzbekistan to introduce a video surveillance system for monitoring the situation in real time remotely during the execution of combat missions (in the direction of reconnaissance, mine-search, finding weapons and explosives) of service dogs in the occupation units.